Communication and information technologies annual : digital empowerment : opportunities and challenges of inclusion in Latin America and the Caribbean - Robinson, Laura; Schulz, Jeremy; Dunn, Hopeton S. (Bingley : Emerald Group Publishing Limited, 2016)
Sponsored by the Communication, Information Technologies, and Media Sociology section of the American Sociological Association (CITAMS), this volume assembles relevant research focusing on ICTs in Latin America and the Caribbean, two understudied areas of global importance. Regarding Latin America, the mobile broadband revolution is taking place and the spread of mobile telephony and broadband Internet is beginning to reach more economically diverse populations. Concerning the Caribbean, this region reflects perhaps the greatest cultural, geographical and linguistic diversity in the Western hemisphere. Because of historical links with Africa, Europe and other metropoles and the region's proximity to the United States and Latin America, the Caribbean offers a unique angle from which to examine the growth of ICTs. The volume features international editorial teams with leading scholars from the Caribbean, Latin America, and North America. Bringing these voices together, the volume sheds light on how existing policies are meeting challenges to digital inclusion, as well as the benefits of connectivity within these societal contexts.
Prelims -- Opportunities and challenges: young people -- Opportunities and challenges: women and gender -- Opportunities and challenges: existing policy frameworks -- Opportunities and challenges: communities and the public sphere.
Includes bibliographical references.
Description based on print version record.
Keywords: Social Science -- Media Studies; Communication studies; Information society -- Latin America; Information technology -- Latin America; Information society -- Caribbean Area; Information technology -- Caribbean Area